Penerapan Push Notification OneSignal Pada System Monitoring Suhu Menggunakan Kodular dan Firebase Berbasis ESP32 - AR, Harlan (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2026)
Existing IoT-based temperature monitoring systems still have a weakness, where users must continuously open the application to monitor temperature conditions. Without an active alert feature, users risk delays in responding to critical conditions if the application is not running. This research aims to develop an active notification feature in an Android application using OneSignal push notifications. The goal is for the system to automatically provide early warnings to users without having to first open the application when temperature or humidity conditions exceed normal limits. The system was built using an ESP32 microcontroller, a DHT11 sensor, and the Firebase Realtime Database. The application development used the Kodular low-code platform integrated with the OneSignal API and Firebase Cloud Messaging (FCM) for notification distribution management. The results of this study show that the developed temperature monitoring application is capable of providing automatic notifications to users without having to run the application. This warning system will be activated if the temperature exceeds 35°C or humidity reaches more than 70%. Based on test data, the push notification feature proved very effective with an average delivery time of only 3.11 seconds, and remains reliable in providing early warnings even when the application is not running. So it can be concluded that the onesignal push notification feature on Kodular can be used to complement the IoT-based temperature monitoring system, as a notification to users if the temperature and humidity exceed the limit.